Awareness of Primary Schools Teachers towards Mumps in Basrah city - Adil Ali Hussein; Sounds Baqer Dawood; Hussein Fakher Kamel (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: Assessment of primary schools teachers’ Awareness towards mumps in Basra cityMethods: A descriptive study was conducted at (9) primary school at Al-Seraghi sectors in BASRA City,from January 14th 2020 to March 12th 2020. A probability stratified random sample of (100) teachers whoteach science subject was selected, and had at employment in the teaching field. A questionnaire formatwas used which was consisted of (2) parts. The overall number of the items included in the questionnairewere (57) items. The first part was related to the demographic data of the teachers, the second part (fivesections) was concerned with teachers’ knowledge about health promotion. Data were analyzed through theapplication of descriptive statistical analysis which included; frequency and percentage, and the applicationof inferential statistical analysis which included; mean of score, and Chi-square test.Results: The study revealed that teachers have acquired good level of knowledge about mumps disease ,medium about method ,symptoms, and control diseases was poor knowledgeConclusions: the relationship between teachers’ knowledge and their demographic characteristics, dataanalysis has showed that there is significant association between teachers’ knowledge mumps except ofyears experiences.Recommendations: The study recommends that there is a need for -oriented education program whichcan be designed, constructed and presented to primary school teachers with great emphasis on all aspectsof steps mumps diseases . Furthermore, teacher can be nominated and encouraged to actively participate ineducation training sessions. Also, the importance of a collaborative work which can be initiated between thehealth Directorate of Education health promotion and the Directorate of primary teaching to create facilitiesfor the implementation of health promotion oriented education program.